2019
DOI: 10.1017/s1368980019002854
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed foods, incident overweight and obesity, and longitudinal changes in weight and waist circumference: the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: Objective: To evaluate the association of ultra-processed food (UPF) consumption with gains in weight and waist circumference, and incident overweight/obesity, in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) cohort. Design: We applied FFQ at baseline and categorized energy intake by degree of processing using the NOVA classification. Height, weight and waist circumference were measured at baseline and after a mean 3·8-year follow-up. We assessed associations, through Poisson regression with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
151
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(186 citation statements)
references
References 50 publications
24
151
0
11
Order By: Relevance
“…A growing number of national and international studies have investigated the impact of food processing on health using the NOVA classification. 6 There is evidence that diets containing a higher share of ultra-processed food have poorer nutritional profiles, 7 and that consumption of such food is directly associated with higher prevalence and risk of overweight and obesity in adults 8,9 and adolescents, 10 as well as with the risk of developing hypertension 11 and cancer in general, especially breast cancer. 12 Studies have already demonstrated its association with abdominal obesity and poorer lipid profiles in children.…”
Section: Diets Containing a Higher Share Of Ultraprocessed Food Havementioning
confidence: 99%
“…A growing number of national and international studies have investigated the impact of food processing on health using the NOVA classification. 6 There is evidence that diets containing a higher share of ultra-processed food have poorer nutritional profiles, 7 and that consumption of such food is directly associated with higher prevalence and risk of overweight and obesity in adults 8,9 and adolescents, 10 as well as with the risk of developing hypertension 11 and cancer in general, especially breast cancer. 12 Studies have already demonstrated its association with abdominal obesity and poorer lipid profiles in children.…”
Section: Diets Containing a Higher Share Of Ultraprocessed Food Havementioning
confidence: 99%
“…First, this is a cross-sectional study, and thus temporality and causality cannot be established. However, our results are biologically plausible and consistent with the randomized controlled trial that has assessed the short-term impact of ultra-processed diets on energy intake and weight gain , and with a few longitudinal studies that have assessed the association between the dietary share of ultra-processed foods and the incidence of obesity or of higher weight gain (Canhada et al, 2019;Rohatgi et al, 2017;. Besides, reverse causality cannot be ruled out.…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with these findings, consumption of ultra-processed foods was found to be associated with 9-year incidence of overweight or obesity in a prospective cohort of Spanish middle-aged adult university graduates , weight gain in a cohort of American pregnant women (Rohatgi et al, 2017), incidence of obesity or of higher weight gain among Brazilian adults (Canhada et al, 2019), and in cross-sectional studies involving nationally representative sample of adults in the U.S. , Canada and Brazil . An ecological study including 19 European countries found a significant positive association between national household availability of ultra-processed foods and national prevalence of obesity among adults (Monteiro et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Several studies have been conducted to quantify the burden of disease attributable to specific UPF consumption. In adults, consumption of UPF has been associated with an increased risk of overweight and obesity (21)(22)(23) , and related conditions, such as hypertension (24) , CVD (25) , as well as higher risk of overall cancer (26) . However, few studies focus on the association between consumption of UPF and risk of diseases in childhood (27)(28)(29) .…”
mentioning
confidence: 99%